Magnetotactic bacteria AMB-1 with active deep tumor penetrability for magnetic hyperthermia of hypoxic tumors. (3rd October 2022) - Chen, Xin; Lai, Liwen; Li, Xiang; Cheng, Xintong; Shan, Xinxin; Liu, Xiangqing; Chen, Liqun; Chen, Guangliang; Huang, Guoming
Abstract : Magnetotactic bacteria AMB-1 bacteria can selectively migrate to hypoxic regions of solid tumors due to their anaerobic characteristics, showing active deep tumor penetrability for efficient magnetic hyperthermia of solid tumor. Abstract : Tumor hypoxia is a great physiological barrier for tumor treatment. The development of efficient detection and treatment methods for tumor hypoxia has great scientific and clinical significance. In this work, we investigated the potential of magnetotactic bacteria AMB-1 for magnetic resonance imaging (MRI)-guided magnetic hyperthermia treatment of hypoxic tumors. Our investigations reveal that AMB-1 bacteria can selectively migrate to the hypoxic regions of solid tumors due to their anaerobic characteristics, showing active deep tumor penetrability. Moreover, AMB-1 bacteria exhibit high MRI contrast and magnetic heating performances because of the excellent magnetic performance of their magnetosomes. In vivo studies demonstrate that AMB-1 can not only generate T 2 -weighted contrast signals in tumor tissue, but also efficiently ablate hypoxic solid tumors through the magnetic hyperthermia effect. We believe that this novel microbial therapy can be a potential weapon for hypoxic tumor treatment.